Maternal sleep deprivation at different stages of pregnancy impairs the emotional and cognitive functions, and suppresses hippocampal long-term potentiation in the offspring rats. Issue 1 (December 2016) - Peng, Yan; Wang, Wei; Tan, Tao; He, Wenting; Dong, Zhifang; Wang, Yu; Han, Huili
Abstract Background Sleep deprivation during pregnancy is a serious public health problem as it can affect the health of pregnant women and newborns. However, it is not well studied whether sleep deprivation at different stages of pregnancy has similar effects on emotional and cognitive functions of the offspring, and if so, the potential cellular mechanisms also remain poorly understood. Methods In the present study, the pregnant rats were subjected to sleep deprivation for 6 h per day by gentle handling during the first (gestational days 1–7), second (gestational days 8–14) and third trimester (gestational days 15–21) of pregnancy, respectively. The emotional and cognitive functions as well as hippocampal long-term potentiation (LTP) were tested in the offspring rats (postnatal days 42-56). Results The offspring displayed impaired hippocampal-dependent spatial learning and memory, and increased depressive- and anxiety-like behaviors. Quantification of BrdU-positive cells revealed that adult hippocampal neurogenesis was significantly reduced compared to control. Electrophysiological recording showed that maternal sleep deprivation impaired hippocampal CA1 LTP and reduced basal synaptic transmission, as reflected by a decrease in the frequency and amplitude of miniature excitatory postsynaptic current in the hippocampal CA1 pyramidal neurons. Conclusions Taken together, these results suggest that maternal sleep deprivation at different stages of pregnancy disrupts the emotional and cognitive functions of the offspring that might be attributable to the suppression of hippocampal LTP and basal synaptic transmission.